2009
DOI: 10.1111/j.1365-2567.2008.03029.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemokines and chemokine receptor expression on tonsillar B cells upon Epstein–Barr virus infection

Abstract: SummaryChemokines and chemokine receptors are likely to play important roles in the pathogenesis of Epstein-Barr virus (EBV) -associated disease. The primary EBV infection occurs in the oropharynx where the virus infects mainly tonsillar B cells. We have previously shown that CXCR4 expression on tonsillar B cells is modulated by EBV. Here, CXCR5 and CCR7 expression, which is important for migration into lymphoid tissue, was followed for 14 days after EBV infection of tonsillar B cells. Early after infection (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…However, some established LMP+ BL lines express CXCR4 that may depend on other EBV proteins in contrast to EBNA2 or LMP1 transfectant, which express only one of the EBV proteins . Primary EBV infection of tonsillar B cells with expression of EBNA2 and LMP1 led to reduction in the expression of CXCR4 and CCR7 . Immunohistochemical studies on chemokine receptor expression in DLBCL reveal that 15/16 expressed CXCR4 and 14/16 were positive for CXCR5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some established LMP+ BL lines express CXCR4 that may depend on other EBV proteins in contrast to EBNA2 or LMP1 transfectant, which express only one of the EBV proteins . Primary EBV infection of tonsillar B cells with expression of EBNA2 and LMP1 led to reduction in the expression of CXCR4 and CCR7 . Immunohistochemical studies on chemokine receptor expression in DLBCL reveal that 15/16 expressed CXCR4 and 14/16 were positive for CXCR5.…”
Section: Discussionmentioning
confidence: 99%
“…CCR7 expression is associated with cancer metastases . We have previously shown that EBV modulates the CXCR4 and CCR7 receptor expression and the corresponding chemokine‐induced migration in primary tonsillar B cells …”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence demonstrates that the regulation of chemokine receptor expression during cell activation or deactivation is an important inducible immune response, often elicited during normal and/or pathologic conditions. For example, Human Herpesvirus 8 (HHV-8) infection alters the chemokine receptor expression in dendritic cells (DCs) and chemokine-induced migration [34]; Platelet-derived CXC chemokine ligand 4 (CXCL4) induces down-regulation of CC chemokine receptors (CCR) 1, −2, and −5, resulting in dramatic impairment of monocyte chemotactic migration towards their cognate CC chemokine ligands (CCL) for these receptors [35]; Primary EBV infection of tonsillar B cells leads to a reduced cell surface expression of CCR7 and CXCR5, as well as to altered expression of several chemokine receptors and chemokines [36]. …”
Section: Discussionmentioning
confidence: 99%
“…B cells display varied responsiveness to chemokines such as B lymphocyte chemokine (BLC/CXCL13), stromal cell-derived factor 1 alpha (SDF-1α/ CXCL12), and secondary lymphoid organ chemokine (SLC/CCL21) during their lifetime (1). Aberrant expression or signaling mediated by chemokines and their cognate receptors have been implicated in the pathogenesis of B cell disorders such as lupus (2), rheumatoid arthritis (3), leukemias (4, 5) and viral infections (6). Chemotaxis occurs when cells respond to gradients of chemokines displayed on endothelial cells lining the blood vessels, or on stromal cells in secondary lymphoid organs (7).…”
Section: Introductionmentioning
confidence: 99%